1978
DOI: 10.3382/ps.0570408
|View full text |Cite
|
Sign up to set email alerts
|

Feed Texture and Light Treatment Effects on the Performance of Chicken Broilers

Abstract: A total of 4800 broiler chicks from a commercial parent genotype was used in two experiments to evaluate effects of feeding finisher diets containing different levels of "fines". These experiments also included a comparison of incandescent continuous green lighting and white lighting with continuous and intermittent exposure at different intensities, including one treatment which was phased down to darkness at 21 days of age and continued to 49 days of age. Fines used in these diets were ground pellets having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 10 publications
3
19
2
1
Order By: Relevance
“…In agreement with the current research, Proudfoot and Sefton [2] evaluated growth and meat yield responses of broilers fed diets containing varying proportions of fines from 28 to 49 d of age. Broilers fed pelleted diets with 0% fines had the highest 49-d BW, whereas cumulative Means within a column without a common superscript differ (P < 0.05).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In agreement with the current research, Proudfoot and Sefton [2] evaluated growth and meat yield responses of broilers fed diets containing varying proportions of fines from 28 to 49 d of age. Broilers fed pelleted diets with 0% fines had the highest 49-d BW, whereas cumulative Means within a column without a common superscript differ (P < 0.05).…”
Section: Discussionsupporting
confidence: 76%
“…Advantages of feeding pelleted diets are improved flowability with mechanical feeding systems, decreased feed wastage, and an enhanced rate and efficiency of growth [2][3][4]13]. The improvement in broiler performance due to pelleting relates to less time devoted to eating translating to reduced energy spent for prehension [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diets fed to the broiler chickens in these experiments were in the ground form; thus, the growth rate was less than that expected for crumbled and pelleted feeds (Proudfoot and Sefton 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently a simple three-stage (starter-grower-finisher) low protein dietary program was developed (Hulan and Proudfoot 1981) (Edwards 1984;Hulan et al 1985Hulan et al ,1986 (Runnels et al 1976;Proudfoot and Sefton 1978;, others (Allred et al 195'7 ;Pepper et al 1960;McNaughton and Reece 1984) have found that when dietary energy was increased by adding up to 5% animal fat, the improvement in feed conversion due to the peieting process was decreased. More iecently, however, a study by Reece et al (1934) This probably reflects the anatomical adaptation of the roaster to mash feeding (Lepkovsky et al 1960;Nir and Nitsan 1979) and the compensatory growth of roasters as discussed elsewhere (Hulan 1985 tend to support this conjecture.…”
mentioning
confidence: 99%